2022
DOI: 10.1152/ajpcell.00451.2021
|View full text |Cite
|
Sign up to set email alerts
|

The CD38 glycohydrolase and the NAD sink: implications for pathological conditions

Abstract: Nicotinamide adenine dinucleotide (NAD) acts as a cofactor in several oxidation-reduction reactions and is a substrate for a number of non-redox enzymes. NAD is fundamental to a variety of cellular processes including energy metabolism, cell signaling, and epigenetics. NAD homeostasis appears to be of paramount importance to healthspan and longevity and its dysregulation is associated with multiple diseases. NAD metabolism is dynamic and maintained by synthesis and degradation. The enzyme CD38, one of the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 330 publications
1
40
0
Order By: Relevance
“…Conversely, cells overexpressing CD38 showed reductions in NAD + levels [ 57 ]. Changes in the expression of CD38 have been proposed to play a major role in NAD + homeostasis in situations of inflammation, aging and senescence [ 58 ].…”
Section: Nad + and Its Decline In Diseasementioning
confidence: 99%
“…Conversely, cells overexpressing CD38 showed reductions in NAD + levels [ 57 ]. Changes in the expression of CD38 have been proposed to play a major role in NAD + homeostasis in situations of inflammation, aging and senescence [ 58 ].…”
Section: Nad + and Its Decline In Diseasementioning
confidence: 99%
“…Recent studies suggested that NAD + -consuming enzymes may also play a regulatory role in aging-mediated NAD + depletion. These NAD + -consuming enzymes are sirtuins, poly (ADP-ribose) polymerases (PARPs), Sterile Alpha and TIR Motif Containing 1 (SARM1), and the ectoenzymes CD38 and CD157 [ 114 , 115 ] .…”
Section: The Balance Between Nad + Biosynthesis An...mentioning
confidence: 99%
“…Decreased cellular NAD + levels also blunt beneficial signaling through sirtuin NAD + -dependent protein deacetylases [ 163 ]. In mice, the decreased NAD + levels that occur with aging are largely due to increased levels and activity of the CD38 enzyme, which is most highly expressed in macrophages and hydrolyzes NAD + as well as its direct precursor nicotinamide mononucleotide (NMN) both intracellularly and extracellularly [ 164 ]. The activity of NAMPT also declines slightly with aging [ 165 ].…”
Section: Interventional Strategies To Correct Dysfunctional Mqc and D...mentioning
confidence: 99%